Development of ways to increase competitiveness of the enterprise - Y. Kulikova; M. Kakushkina; O. Borovikova (Вестник Северо-Кавказского федерального университета, 2022)
With the development of the mechanism of the Russian market, the competitiveness of enterprises and products has become especially noticeable. Indeed, in the absence of a sustainable competitive advantage at the level of each enterprise, it is impossible to create a competitive national economy as a whole. Solving this problem requires all market participants to actively search for new opportunities to increase their competitiveness. The purpose of this study is to develop ways to improve competitiveness based on strategic planning and rating assessment of competitiveness factors. The research results can attract the attention of government bodies at all levels, the scientific community and the expert community, and can also be widely used in research and practice.